New bearings in English studies : a festschrift for C.T. Indra - Indra, C. T.; Azhagarasan, R. (New Delhi : Orient Longman Private Limited, 2008)
Contributed articles on English literature and language; a few on Indic English literature; commemorative volume on the sixtieth birthday of Chidambaram Thathachari Indra, b. 1947, Indian academician.
Includes bibliographical references.
Keywords: English literature -- History and criticism